Effective climatic factors in mountainous regions of Iran for urban planning: a case study in Rudbar Qasran in the Central Alborz. - Saeid Kamyabi,; Shadi Farahani, (Journal of Faculty of Social Sciences and Humanities. Universiti Kebangsaan Malaysia, 2011)
Natural features of a place are considered as a bed for creation and extension of habitat, recognition of living system capabilities will be helpful as a guideline in future planning and elimination of limits and obstacles. The region of our study is situated on the high level of central Alborz. This region is extended from 51˚, 225' to 51˚, 43' in eastern wing of Greenwich Meridian and also 35˚, 47' to 36˚ in the north of equator. Above position includes special climate because of height effect, some of its features are semi mild summers and cold winters and also its variation slope is lower than 1 degree.However Jajorod and Ahar valleys have a great effect on region's ecology but this region is a combined area of mountain and valley. So, height differences affect on temperature variation and slope effects are quite obvious in this region. Besides Jajorod river, earth slope is various from 5 to 51% and a town, Darkia, around this complexity. Generally Geographical directions related to warm and cold slopes ,extended in all four main direction(south, west, east and north), can influence on town construction. This study presents the initial ecological studies in this field, moreover, people are more sensitive in weather changes and ecology situation, so the more we inform about these effects,the better we can manage daily activities. This research attempts to identify the role and impact of natural environmental factors, particularly climatic elements such as effective temperature, rainfall and topography on the physical development , physical cities, particularly cities in the region like Rudbar, Qasran, Oshan and Fasham. In this article, analytical methods, field and library have been used and the results show the most important factors which affect normal physical development such as temperature, ice, rainfall and topography.